Treatment of reactive dyebath wastewater by electrocoagulation process: Optimization and cost-estimation - Aygün, Ahmet; Nas, Bilgehan; Sevimli, Mehmet Faik (Korean Institute Chemical Engineers, 2019)
Reactive dyestuff is commonly used in the textile industry. Reactive dyebath wastewater (RDW) was treated with a batch, monopolar, parallel lab scale electrocoagulation process (EC) having 0.042 m(2) effective electrode area. The effects of process parameters, such as initial pH, current density and electrolysis period on COD and color removal efficiency, were investigated by using response surface methodology (RSM). At the optimal conditions, 85.8% color and 76.9% COD removal were obtained with 1.84 euro/m(3) operating cost for Al electrode, while 92.0% decolorization and 80.9% COD removal were obtained with 1.56 euro/m(3) operating cost for an iron electrode. The iron electrode was found superior to aluminum as a sacrificial anode material in terms of COD and color removal with low cost. The cost of electrical energy, electrode, and chemical consumptions for electrocoagulation were considered to find an optimum and feasible solution. As a result, the operating cost consists of approximately 2% for energy, 28% for electrode and 70% for chemical consumption for both electrodes. Based upon the data, it is clearly seen that operating cost covers mostly for HCI to adjust pH due to the high pH and alkalinity of RDW, which was neglected in many studies. The first-order reaction kinetics with a higher slope for the color were well fitted, resulting in faster color removal than that of COD for both electrodes.
Keywords: Electrocoagulation; Kinetic; Optimization; Operating Cost; Reactive Dye